Functional Verification of a Stainless Steel Reference Block for Calibration of Industrial Ultrasonic Test System - Vera, Jorge; Caballero, Luis; Taboada, Martín; Aguilar, Luis; Briceño, Braulio; Azabache, Eduardo (Civil Engineering Journal, 2026)
In the construction and assembly of metal structures, ultrasonic testing constitutes a pillar for the guarantee of structural integrity. This study aimed to develop and experimentally validate a semi-cylindrical reference block, optimized for the ultrasonic inspection of welds in austenitic stainless steels under the AWS D1.6 code. Unlike conventional devices, this proposal integrates three functional zones into a unified body. Methodologically, the acoustic properties of velocity and attenuation coefficient were characterized using the pulse-echo technique with 2.25 and 5.0 MHz transducers, validating the results through analysis of variance (ANOVA) and Pearson correlation. The findings revealed a statistically significant influence of frequency on the acoustic properties of the material. Functionally, experimental tests demonstrated that the geometric arrangement of three integrated references allows for the efficient construction of Distance-Amplitude Correction (DAC) curves and direct angular verification, overcoming the logistical limitations of conventional prismatic blocks. The main novelty of the device lies in its capacity to unify the functions of sensitivity, resolution, and distance calibration into a single body of acoustically equivalent material, eliminating the need for complex correction factors and ensuring greater precision in industrial inspection.